Segmented phase of ultraviolet (UV) curable thermoset polyurethanes-graphite (TPU-G) composites - M. Rus, Anika Zafiah; Abdullah, Nur Munirah; Abdullah, M. F. L. (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
Segmented thermoset polymeric materials properties mainly classified through its carbonyl hydrogen bonding. The addition of graphite particle loading in polymeric materials tailored the functional characteristic of the composites. Therefore, the carbonyl hydrogen bonding in the hard segments of the synthesized segmented ultraviolet (UV) curable thermoset polyurethanes-graphite (TPU-G) composites was identified. This composites based green polymer incorporated with varying graphite particles loading were prepared through slip casting method which cure upon UV light. These result in an enhancement of the carbonyl hydrogen bonding which tribute to degree of phase separation (DPS %) in the TPU-G composites ranged from 10-20%, as compared to that in the pure TPU. In addition, the spectroscopy detects the formation of carbonyl hydrogen groups within the TPU-G composites although they are prone to chain scission and undergo photo oxidation subjected to ultraviolet (UV) curing. Upon UV curing, higher graphite weight loading (TPU-G20, TPU-G25 and TPU-G30 composites), shows higher and stable DPS% value, attribute to soft segment- soft segment and hard segment- hard segment establishment. Therefore, the graphite particles dominantly absorb the incident radiation instead of thermoset polyurethane without changing its based.